2011
DOI: 10.1093/bja/aer090
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fluid responsiveness in mechanically ventilated children under general anaesthesia using dynamic parameters and transthoracic echocardiography

Abstract: In this study, ▵Vpeak was the most appropriate variable to predict fluid responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(181 citation statements)
references
References 34 publications
6
171
1
3
Order By: Relevance
“…In contrast, Wajima et al 13 examined PVI in preoperative adults and reported no change in PVI or cardiac index after an infusion of 500 mL crystalloid. Pereira de Souza Neto et al 14 noted similar negative findings among intubated children before surgery.…”
Section: Resultsmentioning
confidence: 73%
“…In contrast, Wajima et al 13 examined PVI in preoperative adults and reported no change in PVI or cardiac index after an infusion of 500 mL crystalloid. Pereira de Souza Neto et al 14 noted similar negative findings among intubated children before surgery.…”
Section: Resultsmentioning
confidence: 73%
“…The utility of this method of fluid challenging to determine fluid responsiveness has also been demonstrated in mechanically ventilated children in the postoperative period [40,41] (Fig. 17).…”
Section: Left Ventricular Outflow Tract (Lvot) Velocity Time Integralmentioning
confidence: 90%
“…All patients presented with an intracardiac shunt [5], which can lead to misinterpretation of dynamic indices of preload. Moreover, another study, not quoted in Yin and Ho's meta-analysis, concluded that PVI did not predict response to volume expansion in children [6]. The lack of accuracy of PVI in children could be explained by the changes in arterial, chest wall and lung compliance during childhood [6], and by the influence of age on vasomotor tone.…”
Section: A Replymentioning
confidence: 97%